Thermal Fatigue Resistance of Bionic Compacted Graphite Cast Iron Treated with the Twice Laser Process in Water - Liu, Y.; Zhou, H.; Cheng, J.Y. (Проблемы прочности, 2015)
For enhancing the thermal fatigue resistance of bionic compacted graphite cast iron (CGI) lasertreated in water, the bionic units are treated twice with the laser to form an uneven bionic surface imitating the alternately soft and hard structure of a plant leaf, which can resist the tearing wind. The results show that this method, without changing the phase composition of the bionic unit, makes the austenite-to-martensite transformation more complete and the content of residual austenite is reduced, in addition, the microstructure coarsens and microhardness slightly turns lower. The twice laser process in water can effectively enhance the thermal fatigue resistance of bionic CGI by reducing the number of cracks in bionic units since the number of cross cracks on the bionic unit surface is the key factor, which affects their resistance to thermal crack propagation. For enhancing the thermal fatigue resistance of bionic compacted graphite cast iron (CGI) lasertreated in water, the bionic units are treated twice with the laser to form an uneven bionic surface imitating the alternately soft and hard structure of a plant leaf, which can resist the tearing wind. The results show that this method, without changing the phase composition of the bionic unit, makes the austenite-to-martensite transformation more complete and the content of residual austenite is reduced, in addition, the microstructure coarsens and microhardness slightly turns lower. The twice laser process in water can effectively enhance the thermal fatigue resistance of bionic CGI by reducing the number of cracks in bionic units since the number of cross cracks on the bionic unit surface is the key factor, which affects their resistance to thermal crack propagation.